2021
DOI: 10.1002/cphc.202100111
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Enolization‐Acetaldehyde (CH3CHO) and Vinyl Alcohol (H2CCH(OH)) as a Case Study

Abstract: Owing to the unique conditions in cold molecular clouds, enols—the thermodynamically less stable tautomers of aldehydes and ketones—do not undergo tautomerization to their more stable tautomers in the gas phase because they cannot overcome tautomerization barriers at the low temperatures. Laboratory studies of interstellar analog ices have demonstrated the formation of several keto–enol tautomer pairs in astrochemically relevant ice mixtures over the last years. However, so far only one of them, acetaldehyde−v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…63 Recently, Kleimeier and Kaiser have demonstrated that enolization of acetaldehyde can be induced by 5 keV electron irradiation as proxy for galactic cosmic rays by inter-and intramolecular hydrogen shifts, indicating that this pathway is feasible for the enolization of aldehydes. 64 Based on the infrared spectroscopic detection of the formyl radical, the most plausible reaction leading to 1,2-ethenediol in reactions involving two 13 C 18 O molecules (m/z = 66) is the dimerization of formyl to glyoxal (HCOCHO, 10) followed by reduction through addition of two (suprathermal) hydrogen atoms (pathway 3 in Figure S7; Scheme 1). An experimental study by Chuang et al 65 as well as surface carbon monoxide hydrogenation studies by Fedoseev et al 66 indicate that glyoxal formation from formyl and subsequent hydrogenation are the dominant contributors to glycolaldehyde as well as ethylene glycol formation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…63 Recently, Kleimeier and Kaiser have demonstrated that enolization of acetaldehyde can be induced by 5 keV electron irradiation as proxy for galactic cosmic rays by inter-and intramolecular hydrogen shifts, indicating that this pathway is feasible for the enolization of aldehydes. 64 Based on the infrared spectroscopic detection of the formyl radical, the most plausible reaction leading to 1,2-ethenediol in reactions involving two 13 C 18 O molecules (m/z = 66) is the dimerization of formyl to glyoxal (HCOCHO, 10) followed by reduction through addition of two (suprathermal) hydrogen atoms (pathway 3 in Figure S7; Scheme 1). An experimental study by Chuang et al 65 as well as surface carbon monoxide hydrogenation studies by Fedoseev et al 66 indicate that glyoxal formation from formyl and subsequent hydrogenation are the dominant contributors to glycolaldehyde as well as ethylene glycol formation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Thermodynamically unfavorable molecules such as enols can form at abundances orders of magnitude exceeding those expected due to the nonequilibrium nature of these reactions with excess external energy . Furthermore, GCRs can induce enolization by both inter- and intramolecular hydrogen shifts . In the absence of external energy sources, the low temperatures do not allow the enols to overcome the tautomerization barrier, keeping these reactive species available for (nearly) barrierless reactions to form more complex molecules .…”
mentioning
confidence: 99%
“…13 Furthermore, GCRs can induce enolization by both inter-and intramolecular hydrogen shifts. 14 In the absence of external energy sources, the low temperatures do not allow the enols to overcome the tautomerization barrier, keeping these reactive species available for (nearly) barrierless reactions to form more complex molecules. 15 Thus, far, the only detected tautomer pair in space is acetaldehyde (CH 3 CHO)−vinyl alcohol (H 2 CCHOH).…”
mentioning
confidence: 99%
“…Ground vibrational state anti- and syn- VA were first observed in the ISM by Turner and Apponini, following which potential formation mechanisms were investigated, both in astrophysical ices and in the gas phase. , In this section, we speculate on both the possibility for detecting rotational emission from vibrationally excited syn -VA in the ISM, and on the possibility of observing it in Titans atmosphere.…”
Section: Resultsmentioning
confidence: 93%